Alpha synuclein and inflammaging - Geneviève L. Putnam; Robert W. Maitta (Heliyon)
The α-synuclein protein is an established molecule in Lewy body pathology, especially Parkinson's disease (PD). While the pathological role of α-synuclein (α-syn) in PD has been well described, novel evidence may suggest that α-syn interacts with inflammasomes in response to aging. As age is an inevitable physiological state and is also considered the greatest risk factor for PD, this calls for investigation into how α-syn, aging, and PD could be linked. There is a growing amount of data regarding α-syn normal function in the body that includes involvement in cellular transport such as protein complexes assembly, vesicular trafficking, neurotransmitter release, as well as immune cell maturation. Regarding abnormal α-syn, a number of autosomal dominant mutations have been identified as causes of familial PD, however, symptomatology may not become apparent until later in life due to compensatory mechanisms in the dopaminergic response. This potentially links age-related physiological changes not only as a risk factor for PD, but for the concept of “inflammaging ”. This is defined as chronic inflammation that accompanies aging observed in many neurodegenerative pathologies, that include α-syn's ability to form oligomers and toxic fibrils seen in PD. This oligomeric α-syn stimulates pro-inflammatory signals, which may worsen PD symptoms and propagate chronic inflammation. Thus, this review will explore a potential link between α-syn's role in the immune system, inflammaging, and PD.